Pathogenicity & virulence of Mycoplasma hyopneumoniae - Fernanda M. A. Leal Zimmer (Taylor & Francis Group, 2020)
Mycoplasma hyopneumoniae: is the etiological agent of porcine enzootic pneumonia (EP), a disease that impacts the swine industry worldwide. Pathogen-induced damage, as well as the elicited host-response, contribute to disease. Here, we provide an overview of EP epidemiology, control and prevention, and a more in-depth review of M. hyopneumoniae pathogenicity determinants, highlighting some molecular mechanisms of pathogen-host interactions relevant for pathogenesis. Based on recent functional, immunological, and comparative “omics” results, we discuss the roles of many known or putative M. hyopneumoniae virulence factors, along with host molecules involved in EP. Moreover, the known molecular bases of pathogenicity mechanisms, including M. hyopneumoniae adhesion to host respiratory epithelium, protein secretion, cell damage, host microbicidal response and its modulation, and maintenance of M. hyopneumoniae homeostasis during infection are described. Recent findings regarding M. hyopneumoniae pathogenicity determinants also contribute to the development of novel diagnostic tests, vaccines, and treatments for EP.